Prevalence, Diagnostics and Treatment of Small Intestinal Bacterial Overgrowth in the Clinical Practice in Southern Federal District of the Russian Federation - N. V. Korochanskaya; I. L. Kliaritskaya; S. N. Serikova; A. V. Tkachev; M. V. Koroleva; M. A. Basenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to optimize the provision of medical care to patients with small intestinal bacterial overgrowth (SIBO) in the Southern Federal District based on clarification of data on the epidemiology of the syndrome (disease), unification of approaches to diagnostics and treatment.Materials and methods. We analysed the questionnaires sent to the main gastroenterologists of the federal subjects included in the Southern Federal District, which contained questions in epidemiology, diagnostics and treatment SIBO in different districts.Results. A survey of chief gastroenterologists of the Southern Federal District has demonstrated that there is no accurate data on the prevalence of SIBO in the Southern Federal District. Verification of the diagnosis in all regions is carried out using various modifications of the breath test. Most often, SIBO is suspected and patients with functional gastrointestinal diseases (32.4 %) and diverticular disease (36.5 %) are sent for a breath test. In the group of people with a predominance of hydrogen-producing microbiota, there are fewer men than women (30.8 % vs. 69.2 %), in the group with a predominance of methane-producing microflora, the ratio of men and women was 27.4 % vs. 72.6 %, and in the group with a predominance of hydrogen- and methane-producing microbiota, this ratio was 16.6 % vs. 83.4 %, respectively.Antibacterial therapy after confirmation of the diagnosis is carried out in accordance with national clinical guidelines; probiotics, mainly Saccharomyces boulardii, are prescribed to prevent antibiotic-associated diarrhea.Conclusions. The widespread introduction of various versions of the breath test into the work of healthcare institutions will make it possible to overcome diagnostic difficulties in relation to verification of this diagnosis, substantiate and individualize the approach to prescribing antibacterial and probiotic therapy.